Victimology: theories and applications - Burgess, Ann Wolbert (Jones & Bartlett Learning, 2019)
"Victimology: Theories and Applications introduces readers to the study of victimization, crime typologies, and the impact of crime on victims, offenders, and society at large. Each chapter provides a typology of the offender to analyze motivation. An overview of the issues impacting victims of a wide variety of traditional and contemporary crimes are examined, including child maltreatment, intimate partner violence, elder abuse, cyber crime and hate crimes. The history and theories of victimology are explored, as well as definitive laws and policies, strategies for intervention, and future research areas"--